2011
DOI: 10.1098/rstb.2011.0166
|View full text |Cite
|
Sign up to set email alerts
|

Radial distance determination in the rat vibrissal system and the effects of Weber's law

Abstract: Rats rhythmically tap and brush their vibrissae (whiskers) against objects to tactually explore the environment. To extract a complex feature such as the contour of an object, the rat must at least implicitly estimate radial object distance, that is, the distance from the base of the vibrissa to the point of object contact. Radial object distance cannot be directly measured, however, because there are no mechanoreceptors along the vibrissa. Instead, the mechanical signals generated by the vibrissa's interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 45 publications
2
61
0
Order By: Relevance
“…Previous studies have suggested that the primary importance of whisker taper is that it alters the angle at which a whisker will slip off an object [22,23]. We suggest that an equally important reason is that taper is essential for producing unique mappings between mechanical signals at the whisker base and the 3D contact point [6,30].…”
Section: F Contour Extraction Using Continuous Sweeps Of the Whiskermentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that the primary importance of whisker taper is that it alters the angle at which a whisker will slip off an object [22,23]. We suggest that an equally important reason is that taper is essential for producing unique mappings between mechanical signals at the whisker base and the 3D contact point [6,30].…”
Section: F Contour Extraction Using Continuous Sweeps Of the Whiskermentioning
confidence: 99%
“…A whisker's trajectory along a surface is strongly influenced by friction, texture, surface defects, and local slope: the present work offers an approach to reduce the influence of these variables for contour extraction. Rates of change in bending moment could then be used to sense object motion or object compliance [6,29,30].…”
Section: F Contour Extraction Using Continuous Sweeps Of the Whiskermentioning
confidence: 99%
“…Under these two conditions, a tapering antenna will produce very different curvature profiles along its length, thus mechanically simplifying discrimination of stimuli. Interestingly, tapering in rat whiskers can improve the reliability of information during slower feature extraction tasks Pammer et al, 2013;Solomon and Hartmann, 2011;Williams and Kramer, 2010), and we suspect that similar principles apply to exploratory object localization with antennae. Using the physical model with tunable flexural stiffness, we found that the preview distance was longer for a decreasing stiffness compared with a constant stiffness profile (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…the distance from the base of the whisker shaft to where it was deflected against the surface). In their contribution, Solomon & Hartmann [39] survey a number of different methods that could be applied to compute radial distance based on whisker bending as detected at the base of the whisker within the follicle. A general principle in psychophysics, owing to the experimental psychologist Ernst Weber, is that the 'just noticeable difference' in the change in the magnitude of a stimulus is proportional to the size of the initial stimulus.…”
Section: Contents Of Theme Issuementioning
confidence: 99%